Pengaruh Gaya Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kinerja Karyawan - ., Hairudinor; Utomo, Setio; ., Humaidi (Sam Ratulangi University, 2020)
The purpose of this research is to study and analyze the effect of transformational leadership style, organizational culture, and work environment on employees' performance at PT. PLN (Persero) Rayon Puruk Cahu simultaneously or partially. These samples included 67 respondents who were determined by sampling saturated. Data were collected by questionnaire and then the results were analyzed using multiple linear regression analysis. The results showed that (1) Partial, transformational leadership style variable effect is not significant to the variable performance of employees of PT. PLN (Persero) Rayon Puruk Cahu. (2) Partial, organizational culture variables that significantly influence the performance of employees of PT. PLN (Persero) Rayon Puruk Cahu. (3) Partial, work environment variables significantly affect the performance of employees of PT. PLN (Persero) Rayon Puruk Cahu. (4) Simultaneously or together, the variables of transformational leadership style, organizational culture, and working environment have a significant effect on the performance of employees of PT. PLN (Persero) Rayon Puruk Cahu. (5) Of the three most dominant influences variable is the variable of organizational culture.